Pharmacology and pharmacokinetics of vitamin E: nanoformulations to enhance bioavailability - Mohd Zaffarin, Anis Syauqina; Shiow, Fern Ng; Ng, Min Hwei; Hassan, Haniza; Alias, Ekram (Dove Press, 2020)
Vitamin E belongs to the family of lipid-soluble vitamins and can be divided into two groups, tocopherols and tocotrienols, with four isomers (alpha, beta, gamma and delta). Although vitamin E is widely known as a potent antioxidant, studies have also revealed that vitamin E possesses anti-inflammatory properties. These crucial properties of vitamin E are beneficial in various aspects of health, especially in neuroprotection and cardiovascular, skin and bone health. However, the poor bioavailability of vitamin E, especially tocotrienols, remains a great limitation for clinical applications. Recently, nanoformulations that include nanovesicles, solid-lipid nanoparticles, nanostructured lipid carriers, nanoemulsions, and polymeric nanoparticles have shown promising outcomes in improving the efficacy and bioavailability of vitamin E. This review focuses on the pharmacological properties and pharmacokinetics of vitamin E and current advances in vitamin E nanoformulations for future clinical applications. The limitations and future recommendations are also discussed in this review.